MEMPERKUAT TANGGA DRAMATIK FILM “SENANG BERTEMU DENGANMU” MELALUI PENERAPAN EDITING ASPEK RITMIK - I Gusti Ngurah Agung Jaya Pangestu Suastika; Nyoman Lia Susanthi; Gede Basuyoga Prabhawita (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The fictional film entitled “Senang Bertemu Denganmu” describe the inner conflict of a young man after getting to know someone without an encounter. The young man also got several answers to questions that he had not known throughout his life. The inner conflict is illustrated by the graphic of Hudson's story. There are 6 acts in the graphic so the editor must be able to adjust the rhythm in each scene to strengthen the dramatic ladder of the film. The formulation of the problem that arises is how to apply the rhythmic aspect of editing to strengthen the dramatic ladder of the film "Senang Bertemu Denganmu". The purpose of this creation is to find out the application of editing theory, especially the rhythmic aspect to strengthen the dramatic ladder in the film. Theoretically, this creation can provide benefits in the form of insight in applying rhythmic aspect editing to a film work. In this creation, a data collection method in the form of observation was carried out by reviewing several film and library research. The method of creation of course through the stages of pre-production, production and post-production. The theory of rhythmic aspect of editing is the main theory used. This theory allows the editor to set the length of the short duration of a shot. The editor uses the duration of the shot to emphasize a certain moment so that the information in a shot can be conveyed properly to the audience. This theory is supported by timing and pacing theory. The results of the application of rhythmic aspect editing are found in 9 scenes which are divided into each round of the film. The editing rhythm gives a deeper impact to the characters in the film. When the character feels lonely, it is described with a slow rhythm to emphasize the inner conflict that is being experienced. On the other hand, when the character is experiencing anxiety, the cutting and moving shots quickly is done to impress the character's emotional leap. With various shot durations, the rhythm of editing from the introduction to the end can help to strengthen the dramatic ladder in the film.